PENGEMBANGAN VIDEO ANIMASI NILAI-NILAI PANCASILA SEBAGAI MEDIA PENGUATAN KARAKTER SISWA KELAS II SD INPRES MAWANG KABUPATEN GOWA - Rahmawati Patta; Siti Raihan; Rahmawati Amir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to develop an animated video media of Pancasila values ​​as a medium for strengthening the character of the second grade students of SD Inpres Mawang, Gowa Regency. The type of research used is Development Research (R&D) using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The instrument in this study used a questionnaire aimed at media experts and material experts to assess the validity of the product, and was addressed to students and teachers to assess the feasibility of the product. The results of the validation by media experts on animated videos obtained very valid criteria. The results of the validation by material experts on animated videos obtained very valid criteria. The results of student responses/responses obtained very decent criteria. While the results of the teacher's response/response obtained very decent criteria. With the results of this study, it can be an additional reference for further research and become an innovation in developing learning media, especially in elementary school.